Structural, optical and electrical characteristics of silver ions irradiated ZnO film on flexible substrate. (August 2020) - Imran, M.; Ahmad, R.; Afzal, Naveed; Rafique, Mohsin; Akram Raza, Muhammad; Khaliq, Zubair
Abstract: Zinc oxide (ZnO) films were coated on flexible Polyethylene Terephthalate (PET) substrate by direct current magnetron sputtering of zinc in the presence of reactive oxygen. Afterward, the films were irradiated with 300 keV silver ions (Ag +1 ) through Pelletron Accelerator by changing irradiation dose from 1 × 10 11 to 1 × 10 14 ions/cm 2 in four equal steps. The penetration depth of Ag +1 inside the film was found to be about 70 nm by SRIM (stopping and range of ions in matter) software. Structural parameters of unirradiated and irradiated films were examined by X-ray diffraction. The comparison showed significant degradation of ZnO (002) peak intensity and increase in its widening after irradiation. The Ag +1 irradiation of ZnO at 1 × 10 11 ions/cm 2 decreased its lattice constant (c). However, the lattice constant was increased with a further increase of the irradiation dose. The absorption edge of ZnO was shifted to higher wavelengths with the increase of Ag +1 dose, as shown by the ultraviolet–visible absorption spectra. The Four Probe measurement revealed a consistent decrease in the electrical resistivity of ZnO after Ag +1 irradiation up to 1 × 10 13 ionscm −2 . Then it remained constant with a further increase of the ions dose. Highlights: ZnO films were deposited on PET substrate by DC magnetron sputtering. 300 KeV Silver (Ag) ions were implanted in the films at different doses. The films 'crystallinity decreased due to damage produced by Ag implantation. The Ag ions irradiation of ZnO up to 10 13 decreased its electrical resistivity.